2018
DOI: 10.1016/j.neuron.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic Circuits for Predation and Evasion

Abstract: The interactions between predator and prey represent some of the most dramatic events in nature and constitute a matter of life and death for both sides. The hypothalamus has been implicated in driving predation and evasion; however, the exact hypothalamic neural circuits underlying these behaviors remain poorly defined. Here, we demonstrate that inhibitory and excitatory projections from the mouse lateral hypothalamus (LH) to the periaqueductal gray (PAG) in the midbrain drive, respectively, predation and eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
187
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(196 citation statements)
references
References 53 publications
8
187
0
1
Order By: Relevance
“…Our results fit within a broader field of work that has established the hypothalamus can drive behaviors on a much faster timescale than previously appreciated, including fighting, mating, hunting, and escape (Lin et al, 2011;Lee et al, 2014;Füzesi et al, 2016;Li et al, 2018;Wang et al, 2019). Our work contributes to these efforts by demonstrating that neurosecretory cell types in the vertebrate hypothalamus are capable of generating avoidance behavior in response to stressors, through a convergent hypothalamus-brainstemspinal pathway.…”
Section: Discussionsupporting
confidence: 84%
“…Our results fit within a broader field of work that has established the hypothalamus can drive behaviors on a much faster timescale than previously appreciated, including fighting, mating, hunting, and escape (Lin et al, 2011;Lee et al, 2014;Füzesi et al, 2016;Li et al, 2018;Wang et al, 2019). Our work contributes to these efforts by demonstrating that neurosecretory cell types in the vertebrate hypothalamus are capable of generating avoidance behavior in response to stressors, through a convergent hypothalamus-brainstemspinal pathway.…”
Section: Discussionsupporting
confidence: 84%
“…The central amygdala (CeA) displays activity changes during hunting (Comoli et al , 2005) and optogenetic activation of the CeA→ventral PAG pathway motivates prey pursuit (Han et al , 2017). Stimulation of the medial preoptic area to vPAG pathway promotes acquisition/handling (grabbing, biting) of objects, including prey (Park et al , 2018), and activation of a GABAergic projection from lateral hypothalamus to lateral/ventrolateral PAG motivates attack on prey (Li et al , 2018). In these studies, predatory behaviour was induced in the presence of prey/prey-like stimuli, suggesting these pathways serve to motivate, rather than command, hunting.…”
Section: Discussionmentioning
confidence: 99%
“…Comoli et al (2005)]. Although electrical stimulation of brain regions, including the optic tectum, can evoke hunting actions (Ewert, 1970; Bels et al , 2012) and recent studies in rodents have identified circuits that motivate predatory behaviour (Han et al , 2017; Li et al , 2018; Park et al , 2018), neurons that command vertebrate hunting have yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…It would make sense for LH neurons to be synaptically connected to each other, forming inhibitory and excitatory connections, as these microcircuits could help integrate and filter sensory information and activate populations as a unit (Karnani et al, 2020). Furthermore, they could allow coordinating activity between LH cell types, some of which have mutually exclusive behavioural effects, such as LH glutamatergic vglut2 and GABAergic VGAT neurons (Jennings et al, 2013(Jennings et al, , 2015Li et al, 2018;Stamatakis et al, 2016), and orexin (orx) and melanin concentrating hormone (MCH) neurons (Adamantidis et al, 2007;Jego et al, 2013;Konadhode et al, 2013). Mutual inhibitory coordination of such behavioural control nodes has been a long-standing hypothesis (Tinbergen, 1951).…”
Section: Introductionmentioning
confidence: 99%